2016
DOI: 10.1021/acs.jchemed.6b00298
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Students’ Mechanistic Reasoning about London Dispersion Forces

Abstract: Characterizing how students construct causal mechanistic explanations for chemical phenomena can provide us with important insights into the ways that students develop understanding of chemistry concepts. Here, we present two qualitative studies of undergraduate general chemistry students' reasoning about the causes of London dispersion forces in nonpolar species such as helium atoms. In the first study, we used semi-structured interviews to examine students' verbal explanations for how and why electrical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
141
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(143 citation statements)
references
References 26 publications
2
141
0
Order By: Relevance
“…Rather, worked examples should focus on hydrogen bonds and van der Waals interactions, as our data show that students’ memorized definitions are not adequate for protein structure–function problem solving. This finding is consistent with the literature . Alternatively, preparation for future learning activities could be designed that direct students’ attention to the same problem features, yet give them opportunities to activate their prior knowledge before being asked to solve a problem.…”
Section: Discussionsupporting
confidence: 88%
“…Rather, worked examples should focus on hydrogen bonds and van der Waals interactions, as our data show that students’ memorized definitions are not adequate for protein structure–function problem solving. This finding is consistent with the literature . Alternatively, preparation for future learning activities could be designed that direct students’ attention to the same problem features, yet give them opportunities to activate their prior knowledge before being asked to solve a problem.…”
Section: Discussionsupporting
confidence: 88%
“…The specific connections or relationships that students establish between concepts and ideas are indicative of their reasoning sophistication. A variety of authors have explored the nature of these relationships seeking to characterise different types of reasoning (Tamir, 1991;Assaraf and Orion, 2005;Sevian and Talanquer, 2014;Becker et al, 2016;Weinrich and Talanquer, 2016). These studies have shown that student reasoning may range from merely descriptive to mechanistic for individuals at the same educational level.…”
Section: Exploring Causal Reasoningmentioning
confidence: 99%
“…In recent years, there has been increased interest in better characterising and fostering students' ability to generate causal mechanistic explanations (Grotzer, 2003;Russ et al, 2008Russ et al, , 2009Becker et al, 2016;Southard et al, 2017;Talanquer, 2018). These types of explanations are a hallmark of scientific reasoning and students are expected to generate them using normative concepts and ideas (NRC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown that construct maps are productive tools for assessing the development of students' knowledge and skills in chemistry (Becker, Noyes, & Cooper, ; Becker, Rupp, & Brandriet, ; Brandriet, Rupp, Lazenby, & Becker, ; Claesgens, Scalise, Wilson, & Stacy, ; Loertscher, Lewis, Mercer, & Minderhout, ; Sevian & Talanquer, ). We thus expect that the set of proposed construct maps will be useful for informing assessment of epistemic knowledge of modeling for both traditional and modeling‐focused curricula.…”
Section: Research Questionmentioning
confidence: 99%
“…A construct map is defined by Wilson (, p. 3) as:
“a well thought out and researched ordering of qualitatively different levels of performance focusing on one characteristic. Thus, a construct map defines what is to be measured or assessed in terms general enough to be interpretable within a curriculum and potentially across curricula, but specific enough to guide the development of the other components.”
Researchers have developed and used construct maps as assessment tools in a variety of studies (e.g., Arya & Maul, ; Becker et al, , ; Brandriet et al, ; Briggs, Alonzo, Schwab, & Wilson, ; N. J. Brown, Furtak, Timms, Nagashima, & Wilson, ; Claesgens et al, ; Loertscher et al, ; Rivet & Kastens, ; Schwarz et al, ; Sevian & Talanquer, ).…”
Section: Literature Backgroundmentioning
confidence: 99%